Variation of DNA copies number in etiology of congenital heart defects - A. A. Slepukhina; I. N. Lebedev; G. I. Lifshitz (Российский кардиологический журнал)
Past decade, there is a remarkable evidence of that the variation of DNA copies number (copy number variation, CNV) is related with onset of inborn heart defects (IHD). The review is focused on an impact of CNV in IHD development. Attention is paid on widely known variations, as the microdeletions of 22q 11 chromosome region, as the novel unique variations that were discovered recent years. We assume that common regard on causation of CNV includes a description of their part and characteristics of the pathology caused. Special place does take the analysis of candidate genes in IHD etiology and mechanisms of their pathological influence under the circumstances of gene doses change. A discussion provided on which genetic characteristics of CNV are more informing in assessment of probable pathogenicity of microstructural chromosomes recomposition.